Determination of bunch component which contribute with oil-to-bunch (O/B) ratio of commercial production in Sime Darby Banting / Muhammad Shukri Jumali - Jumali, Muhammad Shukri (Faculty of Plantation and Agrotechnology, 2015)
Analysis of bunch components on oil palm (Elaeis guineensis) have been conducted from October 2014 to May 2015 to determine the trend of each bunch components that might contribute to the oil-to-bunch (O/B) production through all of the bunch components relationship. The raw data was obtained from Sime Darby research centre at Banting, Selangor. The raw data contains 13 th year of research on the bunch analysis. The bunch analysis were collected from two different plots in order to gain more data which at the same time it will give higher amount of significant data. Although the data is taken from different plot, but they were identical characteristics such type of soil, used varieties (tenera) and also the management practices. The first analysis that have been done was trends of each bunch components as the ratio of oil-to- bunch (%) which it was measure as response variable. There are eight type of bunch components that have been considered, which are; fruit-to-bunch (FIB), mean fruit weight (MFW), mesocarp-to-fruit (M/F), kerne]-to-fruit (K/F), shell-to-fruit (S/F), oil-to-dry mesocarp (O/DM), oil-to-wet mesocarp (O/WM) and kernel-to-bunch (K/B). Based on the result it can be seen the major bunch components conduct for the production was fruit-to-bunch (F/B) as it will assign other trend of bunch components allocated